The Influence of Parenting Patterns on the Mental Health of School-Age Children - Shofwan, Arif Muzayin; Akhtar, Shazia; Amin, Rafiullah (Yayasan Pendidikan Islam Daarut Thufulah, 2025)
Background. Parenting patterns play a critical role in the mental health and well-being of children, particularly during the school-age years when they experience significant emotional and social development. The way parents interact with their children, provide support, and set boundaries can either foster resilience or contribute to mental health challenges. Purpose. This study examines the influence of various parenting patterns—authoritative, authoritarian, permissive, and neglectful—on the mental health of school-age children. Method. The primary objective is to investigate how these parenting styles affect children’s emotional regulation, self-esteem, anxiety levels, and overall mental well-being. A quantitative research design was employed, using surveys administered to 400 parents of school-age children, complemented by psychological assessments of their children’s mental health. Results. The results indicate that authoritative parenting is positively associated with better mental health outcomes, including higher self-esteem and lower anxiety levels. In contrast, authoritarian and neglectful parenting were linked to increased anxiety and lower emotional regulation in children. Conclusion. The study concludes that parenting patterns significantly influence the mental health of school-age children, highlighting the importance of supportive, balanced parenting approaches. Interventions aimed at promoting authoritative parenting could contribute to improved mental well-being in children, particularly in academic and social contexts.